2021
DOI: 10.1177/0891988720988901
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Feasibility of a Mindfulness Intervention Delivered via Videoconferencing for People With Parkinson’s

Abstract: Mindfulness-based group therapy is a rapidly growing psychological approach that can potentially help people adjust to chronic illness and manage unpleasant symptoms. Emerging evidence suggests that mindfulness-based interventions may benefit people with Parkinson’s. The objective of the paper is to examine the appropriateness, feasibility, and potential cost-effectiveness of an online mindfulness intervention, designed to reduce anxiety and depression for people with Parkinson’s. We conducted a feasibility ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 61 publications
2
48
0
1
Order By: Relevance
“…Our PD sample size was small ( n = 22). This was similar to prior MBI studies in PD, including MBCT (Birtwell et al, 2017 ; Cash et al, 2016 ; Dissanayaka et al, 2016 ; Fitzpatrick et al, 2010 ; Pickut et al, 2015 ; Rodgers et al, 2019 ), except for the previous online MBCT RCT that enrolled 60 people, 30 in the active arm and 30 in the waitlist/control arm (Bogosian et al, 2022 ).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our PD sample size was small ( n = 22). This was similar to prior MBI studies in PD, including MBCT (Birtwell et al, 2017 ; Cash et al, 2016 ; Dissanayaka et al, 2016 ; Fitzpatrick et al, 2010 ; Pickut et al, 2015 ; Rodgers et al, 2019 ), except for the previous online MBCT RCT that enrolled 60 people, 30 in the active arm and 30 in the waitlist/control arm (Bogosian et al, 2022 ).…”
Section: Discussionsupporting
confidence: 83%
“…In our previous pilot trial, we also found significant pre- to post-PHQ-9 score reductions only; that study was completed just as the COVID-19 pandemic was starting in the USA and our participants (many of them aging adults) were understandably very anxious (Seritan et al, 2021 ). The only other online MBCT trial published to date did not yield any significant differences in mood or anxiety measures (Bogosian et al, 2022 ). Of note, all previous studies, as well as our own, used adapted MBCT protocols.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Corroborando com esses achados, ECR realizado com participantes portadores de esclerose múltipla, em que a intervenção foi um programa online baseado em mindfulness demonstrou ser viável e aceitável, uma vez que 87% dos participantes completaram as oito semanas do programa online (Dunne et al, 2020). Outro estudo com pacientes com Parkinson, em que foi ministrada intervenção com mindfulness via internet, constatou que 73,3% dos participantes aderiram a quatro ou mais das oito sessões o que demonstrou a viabilidade da pesquisa (Bogosian et al, 2021).…”
Section: Discussionunclassified